2015
DOI: 10.1080/15685551.2015.1041075
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of gelatin-tamarind gum/carboxymethyl tamarind gum based phase-separated hydrogels: a comparative study

Abstract: The purpose of this research was to synthesize and characterize gelatin and tamarind gum (TG)/carboxymethyl tamarind (CMT) gum-based phase-separated hydrogels. The hydrogels were thoroughly characterized using bright-field microscope, FTIR spectroscope, differential scanning calorimeter, mechanical tester, and impedance analyzer. The mucoadhesivity, biocompatibility, and swelling property of the hydrogels were also evaluated. The antimicrobial efficiency of ciprofloxacin (model antimicrobial drug) loaded hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…It has been used in the development of various drug delivery systems due to its hydrophilic and bioadhesive properties [21][22][23][24][25][26][27] . Although TG shows presence of non-sterically hindered hydroxyl groups, very few reports mentioned the use of pure TG in chemically crosslinked hydrogels [28] . Moreover, TG can be used as a cheaper alternative to HEC for the preparation of citric acid crosslinked CMC-based hydrogels.…”
Section: Research Papermentioning
confidence: 99%
“…It has been used in the development of various drug delivery systems due to its hydrophilic and bioadhesive properties [21][22][23][24][25][26][27] . Although TG shows presence of non-sterically hindered hydroxyl groups, very few reports mentioned the use of pure TG in chemically crosslinked hydrogels [28] . Moreover, TG can be used as a cheaper alternative to HEC for the preparation of citric acid crosslinked CMC-based hydrogels.…”
Section: Research Papermentioning
confidence: 99%
“…The estimation of the effect of the phenomenon may be predicted from the Weichert model (Figure 3(f )) (Equation (5)). [37] The percentage of SR (%SR; Equation (4)) for F1, F2, F3, F4, F5, and F6 was 54.68, 69.54, 59.99, 61.93, 70.23, and 58.46%, respectively. The result suggested that, in general, there was an increase in the SR when PLLA was introduced into the scaffolds.…”
Section: Swelling Studymentioning
confidence: 99%
“…[46][47][48][49][50] Because of these properties, it is also in preparation of hydrogels. [51][52][53] Tamarind seed polysaccharide is found non-irritant with haemostatic activity. 54 It has shown hepatoprotective activity also.…”
Section: Chemical Composition and Propertiesmentioning
confidence: 99%